1998
DOI: 10.1016/s0167-2789(98)00115-8
|View full text |Cite
|
Sign up to set email alerts
|

Superlattice patterns in surface waves

Abstract: International audienceWe report novel superlattice wave patterns at the interface of a fluid layer driven vertically. These patterns are described most naturally in terms of two interacting hexagonal sublattices. Two frequency forcing at very large aspect ratio is utilized in this work. A superlattice pattern (“superlattice-I”) consisting of two hexagonal lattices oriented at a relative angle of 22° is obtained with a 6:7 ratio of forcing frequencies. Several theoretical approaches that may be useful in unders… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
218
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(232 citation statements)
references
References 16 publications
12
218
2
Order By: Relevance
“…The observed superlattice pattern is similar but different from the ones previously observed by others [3][4][5][6]. In particular, the snapshot of superlattice [ Fig.…”
contrasting
confidence: 77%
See 1 more Smart Citation
“…The observed superlattice pattern is similar but different from the ones previously observed by others [3][4][5][6]. In particular, the snapshot of superlattice [ Fig.…”
contrasting
confidence: 77%
“…In subsequent experiments on a similar experimental setup, Kudrolli et al observed two different types of superlattice pattern ("type-I" and "type-II") in addition to the 12-fold symmetric quasicrystalline pattern [3]. More recently, Arbell and Fineberg report yet another kinds of superlattice pattern ("SSS" and "2MS") [4].…”
mentioning
confidence: 93%
“…The resulting pattern is composed of two discrete but interacting sublattices and thus presents a spatial order on two different length scales. Such dynamic superlattices have also been obtained in nonlinear optical devices [Pampaloni et al, 1997;Musslimani & Pismen, 2000] and in two-frequencies Faraday experiments [Kudrolli et al, 1998;Arbell & Fineberg, 1998]. Finally, for specific relations between the angles of the triads of wave vectors of active modes, quasiperiodic patterns may also be generated.…”
Section: Turing Patternsmentioning
confidence: 84%
“…In large domains recent work has focused on two-frequency forcing [1], in which the two frequency components select distinct wavenumbers. These experiments, generally carried out in quite viscous liquids, have revealed various superlattice patterns, as well as nonperiodic states resembling quasipatterns [12,27,28,1]. In these experiments, the frequencies used are in (low order) resonance, so that the forcing acceleration remains periodic in time, with the frequency ratio, their relative phase, and their relative contribution to the forcing providing parameters to be tuned in the experiment.…”
Section: Introductionmentioning
confidence: 99%